2012
DOI: 10.4103/0019-5413.101034
|View full text |Cite
|
Sign up to set email alerts
|

Role of calf muscle stimulation in the prevention of DVT in Indian patients undergoing surgeries for fractures around the hip

Abstract: Background:The venous stasis of soleal vein during surgery may be an important factor in the development of deep vein thrombosis (DVT). The stimulation of calf muscle during surgery may help in preventing DVT. The present study is conducted to evaluate the role of peroperative calf muscle electrostimulation in prevention of DVT in patients undergoing surgeries around the hip joint.Materials and Methods:The study comprised 200 patients undergoing surgeries around the hip joint. The patients having risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…However, the incidence of DVT in patients with malignant disease was significantly lower Williams et al 23 Geko T-1 1 70-560 ms 2 7 N R Izumi et al 24 SEN-52901 10 NR NR 100 Jawad et al 25 Geko T-1 1 70-560 ms 2 7 N R Warwick et al 35 Geko T-1 1 0-400 ms 2 7 N R Broderick et al 36 Duo Williams et al 23 Izumi et al 24 Jawad et al 25 Goyal et al 26 Velmahos et al 27 Merli et al 29 Bostrom et al 30 Lindströ m et al 28 Doran et al 31 Doran and White 32…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the incidence of DVT in patients with malignant disease was significantly lower Williams et al 23 Geko T-1 1 70-560 ms 2 7 N R Izumi et al 24 SEN-52901 10 NR NR 100 Jawad et al 25 Geko T-1 1 70-560 ms 2 7 N R Warwick et al 35 Geko T-1 1 0-400 ms 2 7 N R Broderick et al 36 Duo Williams et al 23 Izumi et al 24 Jawad et al 25 Goyal et al 26 Velmahos et al 27 Merli et al 29 Bostrom et al 30 Lindströ m et al 28 Doran et al 31 Doran and White 32…”
Section: Discussionmentioning
confidence: 96%
“…The study addresses an appropriate and clearly focused question 23 Izumi et al 24 Jawad et al 25 Goyal et al 26 Velmahos et al 27 Merli et al 29 Bostrom et al 30 Lindströ m et al 28 Doran et al 31 Doran and White 32…”
Section: Discussionmentioning
confidence: 98%
“…12 Agarwala et al, on the other hand showed an incidence of 60% in 50 patients who did not have prophylaxis peri-operatively using venography as the end point. 2 In our series, the incidence of DVT was 7%.…”
Section: Discussionmentioning
confidence: 99%
“…2 In our series, the incidence of DVT was 7%. Most other authors 1,3,4,9,12,19,20,[22][23][24] who have reported a similar incidence had also used Colour Doppler as the end point, rather than venography. Venography may pick up a lot of asymptomatic DVTs, 2,5,7 which may not be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Это может быть объяснением того факта, что ЭМС, применяемое менее, чем 5 раз в день (с временными промежутками, достаточными для образования тромбов), клинически неэффективно. Интраоперационное применение ЭМС является исключе-нием, т. к. в большинстве случаев формирование ТГВ про-исходит во время операции, следовательно, одной сессии может быть достаточно, чтобы существенно сократить частоту развития ранних ВТЭО [27,28]. Некоторый про-цент предотвращения образования тромбов и связанная с ним активация тромболитического каскада могут объ-яснить изменения фактора коагуляции, вызванные ЭМС.…”
Section: механическая перемежающая компрессия нижних конечностейunclassified